Postharvest quality of sweet corn affected by hydro-cooling and packaging type - Ding, Phebe; Abdul Muthlib, Maizan Izni (Malaysian Society of Plant Physiology, 2017)
Sweet corn or scientifically known as Zea mays is a very common horticultural crop in Malaysia. It is among the top ten cash crops planted among growers in Malaysia. The taste and quality of sweet corn depends heavily upon its sugar content. Sweet corn has high respiration rate (Kader, 2002) with rate of 30-51 and 282-435 mg CO2 kg-1h-1 at 0 and 25 C, respectively (Gross et al., 2004). High respiration causes sugar content in the sweet corn to reduce by about 6 and 60% in a single day at 0 and 30 C, respectively (Brecht, 2004). So, the quality of sweet corn will rapidly degrade if not handled properly. Lowering internal commodity temperature following harvest is critical in extending postharvest life. This can be done in two-stage process starting with precooling and low temperature storage. Precooling using water as cooling medium (known as hydro-cooling) is recommended to remove field heat and extend postharvest life for sweet corn (Vigneault et al., 2007). However, lack of proper packaging during storage can cause serious deterioration and loss of tenderness and sweetness of sweet corn (Risse and McDonald, 1990). Thus, proper packaging during storage is essential to retain sweet corn quality. However, there was no literature on the effect of hydro-cooled sweet corn followed by packaging. Therefore, this study was conducted to examine the quality of sweet corn after hydro-cooled and packed using cling wrap and polyethylene bag.